Epidemiology for advanced nursing practice - Macha, Kiran; McDonough, John P. (Jones & Bartlett Learning, 2012)
Epidemiology for Advanced Nursing Practice guides graduate-level nursing students to understand the basic concepts of epidemiology while gaining and applying statistical conceptual skills. Focusing on the importance of disease prevention and community-centered migration, this text helps students expand their knowledge base while enhancing practical application skills and stimulating research interests. Designed to prepare advanced practice nursing students to meet the American Association of Colleges of Nursing (AACN) for Doctor of Nursing Practice (DNP) standards, this text features expert insights, objectives, critical questions, and references. Topics include the role of epidemiology and statistics in advanced nursing practice, study designs and outcomes, emerging infectious diseases, genetic and environmental epidemiology, the role of culture, nursing in pandemics and emergency preparedness, and legal and ethical issues.